RANCANG BANGUN PROTOTIPE PREPARASI MATERIAL RESISTANCE SPOT WELDING - Ariyanto Ariyanto; Iman Pradana A. Assagaf; Rifaldy Ramadhan Latief; Fajar Reski Maulana; Gusrifar Gusrifar; Muh. Aqdar Fitrah; Muhammad Ikhsan (Jurnal Rekayasa Mesin, 2023)
The manufacturing process in the automotive industry is in dire need of resistance spot welding machines. Because it was easier to use, highly effective, and effective in functioning. However, there were sometimes still connection problems that were still of poor quality, both nuggets and areas that are subject to electrode pressure. To get a quality welding connection, a machine was needed that was able to carry out good material preparation in the form of sanding, able to set the welding current analogously, able to set the time with an automatic timer, able to apply pressure on the electrode measurably during the welding process. The research aimed to design a prototype of resistance spot welding material preparation that could adequately carry out material preparation and welding using a Bluetooth system connected to a mobile phone. The research methods carried out were as follows: first, designing the machine using Autodesk Inventor software, then the device was made with a focus on material preparation prototypes, then the machine elements were made for the material clamping rail, then the machine elements in the control section using Bluetooth connected to the mobile phone, the machine was tested, then the connection quality testing process was carried out on the tensile testing machine. The results showed that the design results had been made using elbows and iron plates with threaded rails with a length of 650 mm, which became material clamping rail grooves with a drive using window motors controlled by Bluetooth on the Arduino circuit. The test results of welded joints show that the roughness is 0.20 Î¼m which has the highest tensile strength.